2016
DOI: 10.1186/s13028-016-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Farm characteristics and management routines related to neonatal porcine diarrhoea: a survey among Swedish piglet producers

Abstract: BackgroundIn recent years reports from a number of countries, including Sweden, describe problems with diarrhoea in newborn piglets despite the use of previously effective preventive measures. This seemingly altered disease pattern of neonatal porcine diarrhoea (NPD) warrants investigations on the magnitude and manifestation of the problem. The aim of the present study was to investigate the herd-level prevalence of NPD in Sweden and to describe disease characteristics and intervention strategies used in affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Similarly, E. hirae may induce diarrhoea, weight loss, and rough hair coat in 1-5 day old piglets [18,20,41]. In one study, more than half of the piglets in 1 to 3-day-old litters were affected, and the mortality was <10% [42].…”
Section: Clinical Signsmentioning
confidence: 99%
“…Similarly, E. hirae may induce diarrhoea, weight loss, and rough hair coat in 1-5 day old piglets [18,20,41]. In one study, more than half of the piglets in 1 to 3-day-old litters were affected, and the mortality was <10% [42].…”
Section: Clinical Signsmentioning
confidence: 99%
“…This was in accordance with a recent report on the aetiology of recurrent neonatal diarrhoea in Spain. 14 During recurrent neonatal diarrhoea cases investigation, all risk factors must be reviewed (including vaccination, 15 maternal immunity transfer, sow parity, 16 disease status of the farm, washing and disinfection protocols of the farrowing unit between batch 15 and environmental conditions). Among these critical points, the microbiological quality of liquid feed for sows is investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no other reports in the literature have described the effect of parity on the microbial composition of their offspring. However, several studies have reported increasing cases of diarrhea in litters born to gilts 36,37 , which could be a consequence of a lower microbiota diversity. In general, we found that piglets born to gilts contained less microbial diversity in all treatment groups in the nasal and faecal microbiota, perhaps as a consequence of the antimicrobial treatment performed to gilts for aclimatation to the farm.…”
Section: Discussionmentioning
confidence: 99%